2018
DOI: 10.1590/18069657rbcs20170121
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Variability of Soil Fauna Under Different Land Use and Managements

Abstract: Geostatistics allows the evaluation of the distribution pattern of data with high spatial variability in agricultural systems. This study aimed to evaluate the spatial variability of biological diversity indices of soil fauna under different land (agriculture and forest). Samples were collected in seven areas (millet, soybean, corn, eucalyptus, pasture crops, and preserved and disturbed Cerrado), in Maranhão state, Brazil. The soil fauna was caught trapped in pitfall traps, installed 3 m away from each other. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 45 publications
1
24
0
3
Order By: Relevance
“…Determination of the range values provides an idea of the correlation between different sampling locations, along with the maximum spatial dependence distance between them [ 95 ]. Fluctuation in the range with different lag sizes indicates that spatial structure may merely be regarded with a single model for semivariogram [ 96 ]. This difference may not be important for semivariance calculation, but it may be important if the purpose is to understand the underlying spatial structure of the data [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…Determination of the range values provides an idea of the correlation between different sampling locations, along with the maximum spatial dependence distance between them [ 95 ]. Fluctuation in the range with different lag sizes indicates that spatial structure may merely be regarded with a single model for semivariogram [ 96 ]. This difference may not be important for semivariance calculation, but it may be important if the purpose is to understand the underlying spatial structure of the data [ 97 ].…”
Section: Resultsmentioning
confidence: 99%
“…The area with eucalyptus had values of α 0 greater than 1,000, indicating that the fauna of the soil in this area is more diverse (Shannon -α 0 = 1,132 ± 0,038). The occurrence of higher numbers of invertebrates in the area with eucalyptus can be explained by the higher content of organic material (Table 1 -OM = 27 g•dm -3 ) (Wardle et al 2006;Silva et al 2018). This justifies the dominance of Collembola, which, according to Bardgett and van der Putten (2015), are organisms that only develop in favorable environments with high content of organic matter.…”
Section: Multifractal Analysismentioning
confidence: 87%
“…The natural dynamic of soil fauna is altered with time in agricultural systems. Silva et al (2018) found that the abundance and richness of soil organisms are altered depending on the use and the management. Paul et al (2015) described that conservationist management practices besides improving the physical and chemical quality of the soil, also provided the increment of the soil fauna and other biological attributes.…”
Section: Introductionmentioning
confidence: 99%
“…There are often considerable differences between organic and conventional agriculture in particular conditions, which does not only mean the use of pesticides but also the way the soil is tilled. In some cases these interventions can be quite a harmful factor in terms of biodiversity of soil fauna (Silva et al, 2018). These authors state that physical disturbance (e.g., ploughing) is a key factor affecting biotic activity and species diversity in agroecosystems.…”
Section: Carabid Beetles In Different Crops and Farming Systemsmentioning
confidence: 99%